ANALISIS FINANSIAL PETERNAKAN AYAM PETELUR SUROSO FARM DESA BAKALAN KECAMATAN POLOKARTO KABUPATEN SUKOHARJO - Andhyka Wahyu Pambudi; Agus Setiadi; Warsono Sarengat (MEDIAGRO, 2019)
ABSTRACT The purpose of this research were to know level of profit, capability of getting profit, capability of return investment, time capability of return investment, capability to know ratio of getting profit from production cost on Suroso Farm of layer chicken. The data which to be analyzed was primary data taken from interview and secondary data taken from institution. This research use kind of type financial analyzed Return On Investment (ROI), Payback Periode (PP), dan Benefit Cost Ratio (BC Ratio). The result of analyzed show rate of population Suroso Farm 35.870, ROI 68%, PP value to return investment 1 year and BC ratio 2,6. That means this company Suroso Farm is feasible to be going on and profitable. Keywords: ROI, PP, BC ratio.